PENERAPAN ETIKA BISNIS PADA USAHA KECIL DAN MENENGAH MELALUI PEMANFAATAN COMPUTER MEDIATED COMUNICATION (CMC) DAN MEDIA SOCIAL FACEBOOK DI KOTA MAUMERE - Maria Goreti Mao Tokan; Viktor Eko Transilvanus; Imelda Virgula Wisang (Jurnal Projemen UNIPA, 2025)
In an era of increasingly intense business competition, the ability of Micro, Small, and Medium Enterprises (MSMEs) to maintain and expand their market presence has become crucial. One of the key factors in ensuring business sustainability is the application of business ethics. Business ethics play a significant role in shaping a company's reputation and long-term success. However, ethical challenges in conducting business through social media remain an issue, such as the mismatch between the promoted product and the actual product. This study highlights the importance of applying ethical business principles, such as honesty and transparency, in MSME promotional activities on Facebook to foster consumer trust and ensure business continuity. The research was conducted on two MSMEs in Maumere Hanara Shop and Cicy Lyudia Rahmatun Shop which utilize Facebook as a platform for communication and marketing. The findings reveal that the ethical use of Computer-Mediated Communication (CMC) technology can serve as an effective strategy for strengthening business relationships and building a positive brand image in the eyes of consumers.